Parametric and feasibility study of flexographic printing process for R2R printed electronics - Ee, Jin Hao (2018)
Flexography is most commonly used for printing on non-porous substrates for food packaging. Recent technological advancement in flexographic printing plate production has allow flexography to catch up with other R2R processes such as gravure printing in the printed electronics field. However, there are a lot of parameters involved in flexography that can affect the print quality. This research attempted to achieve finer line printing as compared to the current 45-100µm printed line width range of flexography by studying and manipulating these parameters.